Physicochemical, Antibacterial Studies of Some New Transition Metal Complexes of Chelating Active Compound - Mahasin. F. Alias (Journal of Global Pharma Technology, 2018)
Metal (II) complexes of Co, Ni, and Cu with Amoxicillin derivative [Methyl-6-[2-(benzyl ideneamino) 2-(4-hydroxy phenyl) actamido]-2,2-dimethyl-5-oxo-L-thio-4-azabicyclo[3.2.0] heptan-3-carboxylate], (L) were synthesized and identification by phesio. Chemical procedures i.e (elemental analysis CHNS, metal analysis AA, Uv-Vis, FTIR, TGA, magnetic susceptibility and conduct metric measurement. From analysis the ligand behaves as a bidentate through oxygen carbonyl group of amide and nitrogen atom of imine group. Tetrahedral geometry was suggested for the cobalt ion and a six coordination octahedral geometry for nickel and copper complexes has been proposed. The ligand and its metal complexes were also tested for the Candida albicans .c., and as antibacterial activity to assess their inhibiting potential against two selected microorganism, staphylococcus aureus and Escherichia Coli using two different concentration (10 and 5 mm) in nutrient agar medium.Keywords: Schiff base, Metal complexes, Physico-chemical, Microorganism, Amoxicillin.